An evaluation on consumers' usage pattern of acetaminophen (paracetamol): A multicenter study from Penang, Malaysia - Chee Ping Chong; Seak Fang Tan; Weng-Tink Chooi (Archives of Pharmacy Practice, 2017)
Background: Acetaminophen poisoning is becoming an increasingly common social problem in Malaysia. An understanding of consumers' usage pattern of acetaminophen is essential in addressing the issue of accidental acetaminophen poisoning. This study was therefore aimed to evaluate the usage pattern of acetaminophen among the consumers in the state of Penang, Malaysia. Methods: A survey using a questionnaire was carried out in Health Clinic of University Sciences Malaysia (USM), Outpatient Clinic of Advance Medical and Dental Institute, USM, and five selected community pharmacies in the state of Penang from February 2013 to April 2013. A convenient sample of 400 Malaysian consumers was involved in this study. Results: Majority (98.0%) of the consumers had ever taken acetaminophen. The consumers mostly used acetaminophen for headache (75.0%) and fever (72.8%). The 500 mg acetaminophen tablet was more commonly used among the consumers (94.3%) then the 650 mg tablet (44.3%). A total of 1.1% of the consumers had taken more than two tablets of acetaminophen 500 mg tablet per intake. Meanwhile, 24.4% of the consumers had taken two tablets or more of acetaminophen 650 mg tablet per intake. The consumers mostly consumed acetaminophen in a frequency of either 4 hourly (29.5%), 8 hourly (17.3%) or 6 hourly (14.8%). However, 6.3% and 7.0% of the consumers would increase the dosage or frequency of acetaminophen consumption, respectively, when their conditions or symptoms persisted after taking the acetaminophen. Conclusions: The use of acetaminophen is prevalent among the surveyed consumers. The risks of acetaminophen overdose were found among the consumers.